2013
DOI: 10.3111/13696998.2013.773333
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility of pregabalin as add-on to usual care versus usual care alone in the management of peripheral neuropathic pain in Belgium

Abstract: Based on this analysis, it can be concluded that from a Belgium payer perspective pregabalin offers a slight increase in quality of life in the studied populations as compared to standard care. Pregabalin is cost effective in the majority of cases except in one published clinical study, despite a low incremental cost per year (€300).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Also, we cannot rule out completely that patients who are treated with gabapentin under routine medical practice are difficult to be treated to higher dosages such as the one observed in randomized clinical trial with such drug. The results observed in our retrospective study are consistent with other series published in the scientific literature either in Spain [19,20], and elsewhere as well [21][22][23][24]. All of such references, irrespectively of the economic type of study (cohort observational trial, economic modeling or clinical trial) have shown that in different types of PNP, pregabalin therapy is normally associated with lower healthcare resources utilization and fewer days of sick leave in comparison with gabapentin leading to a lower economic impact to the National Health System budgets, which is relevant when health decision is taken on a routine basis.…”
Section: Discussionsupporting
confidence: 93%
“…Also, we cannot rule out completely that patients who are treated with gabapentin under routine medical practice are difficult to be treated to higher dosages such as the one observed in randomized clinical trial with such drug. The results observed in our retrospective study are consistent with other series published in the scientific literature either in Spain [19,20], and elsewhere as well [21][22][23][24]. All of such references, irrespectively of the economic type of study (cohort observational trial, economic modeling or clinical trial) have shown that in different types of PNP, pregabalin therapy is normally associated with lower healthcare resources utilization and fewer days of sick leave in comparison with gabapentin leading to a lower economic impact to the National Health System budgets, which is relevant when health decision is taken on a routine basis.…”
Section: Discussionsupporting
confidence: 93%
“…It is one of the series with the highest number of subjects studied, which should be interpreted as a study strength 31, 32, 33, 34, 35, 36. However, it should be noted that without appropriate standardization of patient characteristics, as well as in the number and extent of the variables studied, the results obtained should be interpreted with caution, and care should be taken in the external validation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The search identified 797 studies, 20 of which met the inclusion criteria. Of the 20 included studies, 14 presented original model structures 4,5,[16][17][18][19][20][21][22][23][24]27,29,30 , and six used existing model structures populated with data and assumptions that differed from those in the original study 3,25,26,[31][32][33] . Herein, where data and scope are compared, we refer to all 20 included studies, but where model type and structural elements are compared, we compare across the 14 original model structures only.…”
Section: Figure 1 Presents a Preferred Reporting Items For Systematicmentioning
confidence: 99%
“…Results in Table 1 suggest that the volume of cost-effectiveness studies in neuropathic pain is increasing; over 50% of the 20 inclusions (11 studies) were published after January 2010 [3][4][5]17,19,20,25,29,[31][32][33] . This may reflect an emergence of new treatments for neuropathic pain, and an increasing need across jurisdictions to demonstrate cost-effectiveness in order to receive reimbursement for these types of therapies.…”
Section: Figure 1 Presents a Preferred Reporting Items For Systematicmentioning
confidence: 99%
See 1 more Smart Citation